Pope, Council, and the Filioque in Western Theology, 1274–1439 - Schabel, Chris (Medieval encounters, 2015)
The doctrine of the Filioque was officially determined at the Fourth Lateran Council in 1215, at the Second Council of Lyon in 1274 the determination was clarified, and this clarification was repeated in 1439 in the formulation of the Council of Florence. Yet the Filioque was already universally accepted in the Latin West by 1100, while the clarification at Lyon was the general teaching before 1274. Rather than establish doctrine, then, Innocent iii at Lateran iv and Gregory x at Lyon ii merely codified it, offering codifications that were later incorporated into canon law under Gregory ix and Boniface viii, respectively. A survey of several dozen university treatments of the procession of the Holy Spirit between 1274 and 1439 reveals that the conciliar pronouncements under the popes played little role in the discussion, and where they appear, it is usually as a brief statement of what was official. By the late fourteenth century, some theologians doubted that the Filioque as expressed in 1215 and 1274 could be defended rationally, an indication that convincing the Greeks at Florence to accept true dogmatic union would be impossible.